Investigating the exotic magnetic properties in manganese diboride, a borophene intercalation compound - Li, Hui; Cui, Siwen; Huang, Yi; Zhao, Yongsheng; Zhu, Pinwen; Ma, Shuailing (Frontiers in Physics, 2024)
The temperature-dependent magnetic susceptibility combined with first-principle calculations was conducted to unravel the magnetic structure and the magnetic interaction of the laminar structure of manganese diboride (MnB2). MnB2 showed weak ferromagnetic, antiferromagnetic, and paramagnetic behavior with increased temperature. Its weak ferromagnetic property below 135.6 K Curie temperature (TC) originated from the spin canting antiferromagnetic magnetic structure. The exotic kink of temperature-dependent magnetic susceptibility at 330 K Néel temperature (TN) correlated with the transition from antiferromagnetic to paramagnetic structure. First-principle calculation show that the antiferromagnetic ordering show lower energy, and suggest a canting anti-ferromagnetic ordering for its ferromagnetic behavior. The peculiar magnetic behavior of MnB2 may be due to the insertion of the honeycomb boron layers into the host matrix of manganese atoms. The honeycomb boron layers played a key role in the exchange between two manganese layers. This study resolved the longstanding puzzle of the magnetic structure of MnB2 and provided a typical laminar magnetic structure prototype.